A case of loin pain after cardiac catheterisation. Issue 17 (7th April 2016) - Chatterjee, Debjit; Sadiq, Ambreen; Garikipati, Raj
Abstract : Clinical introduction: A 57-year-old woman with known moderate-to-severe mitral stenosis and atrial fibrillation (AF) presented to the emergency department with acute onset right loin pain after having a coronary angiogram and left and right heart catheterisation through the right femoral route about 28 h ago. The cardiac catheterisation was done after she presented with one episode of troponin-negative chest pain and progressive shortness of breath. She had anterior wall myocardial infarction (MI) 25 years ago, which was thought to be due to coronary artery embolism. Her mitral stenosis was diagnosed at that stage. Her warfarin was stopped for 5 days before cardiac catheterisation and international normalised ratio (INR) on the day of the procedure was 1.1. No bridging heparin/low molecular weight heparin (LMWH) was used and warfarin was restarted on the evening of the procedure at the usual dose. Clinical examination revealed some guarding in the right iliac fossa and some tenderness in the right loin. She was not feverish and there was no dysuria or frequency. There was no lump at the puncture site. On presentation to the emergency department, a contrast-enhanced CT scan of the abdomen was performed (figures 1 and 2 ). Question: Which of the following is the aetiology of the pain? Abdominal aortic dissection Renal artery embolism Retroperitoneal haematoma Ureteric stone